Morphological Characteristics and DNA Barcoding of the Rare Blanket Octopus Tremoctopus violaceus (Cephalopoda: Tremoctopodidae) in the Adriatic Sea - Mirela Petrić; Branko Dragičević; Rino Stanić; Željka Trumbić (Diversity, 2023)
Tremoctopods are epipelagic argonautoid octopods characterized by their expanded dorsal webs and strong sexual size dimorphism, with dwarfed males. The scarcity of taxonomic features attributed to this genus presents a challenge, and there is growing evidence of species misidentification in Tremoctopus genus on a molecular level. In this study, we investigated four female specimens of blanket octopus Tremoctopus violaceus caught by purse seine fishing in the Central Eastern Adriatic Sea in 2019. Individuals had smooth, firm and muscular bodies, dark bluish purple on the dorsal and iridescent silvery on the ventral side, with dorsal mantle lengths of 113, 82, 80 and 78 mm. The constructed phylogenetic trees based on the 16S ribosomal RNA and cytochrome c oxidase subunit I sequences of investigated Adriatic specimens and publicly available sequences showed strong support for the T. violaceus clade, consisting of individuals collected from the Adriatic Sea, Mediterranean Sea and Atlantic Ocean, with the exclusion of Indo-Pacific clade most probably corresponding to T. gracilis. To fully understand the life-history traits of Tremoctopus species, future research should focus on DNA-based methods for correct species identification combined with morphological characters, geographic distribution and ecological information.